Students' perceptions of classroom assessment practices in Malaysian Higher Education Institutions - Wan Nadia Asila Tun Ibrahim
This study investigated the students' perceptions of Classroom Assessment Practices (CAPs) in Malaysian Higher Education Institutions (MHEls). The objectives of this study were to explore and investigate the students' perceptions of CAPs and to find out if there is any relationship among the six scales of CAPs, namely, Congruence with Planned Learning (CPL), Authenticity, Students' Consultation (SCON), Transparency, Students' Capabilities (SCAPs) and Students' Soft Skills (SSS). The participants involved in this study were first semester of diploma students in MHEls. The study employed quantitative research method where a questionnaire survey was used and distributed to the participants for data collection. The questionnaire 'The Student Perceptions of Assessment Questionnaire (SPAQ)' used was adapted from Fisher, Waldrip, & Dorman (2005). The data were then computed and analysed by using Statistical Package for Social Sciences (SPSS) software. The findings of the study suggested that students in MHEls agreed the CAPs implemented were congruent with planned learning, authentic and transparent. They probably agreed that CAPs was a mean to consult the lecturers and classmates. The findings also suggested that the students agreed that the CAPs conducted appropriately matched with their level and capability, and have helped them to develop and improve their soft skills. Besides, it was suggested that there was a significant positive correlation among the six scales of CAPs. Finally, recommendations and limitations of this study were also discussed. Key words: Malaysia, Higher Education, Classroom Assessment Practices, Malaysian students